Pendampingan Pembuatan Nomor Induk Berusaha (NIB) dalam Rangka Kesadaran Legalitas pada UMKM Salama Kelurahan Na’e Kota Bima - Irma Mardian; Kartin Aprianti; Wahyu Sa’ban; Susi Susanti; Nurul Istiqamah; Wanda Widiartiningsih; Osfaningsih Osfaningsih; M. Wahyu Hidayat (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
Micro, Small and Medium Enterprises (MSMEs) can be the backbone of a country's economy, because their form of business can revive a declining economy. The method used is to conduct a survey to determine the condition of needs of MSME actors in Salama, Na'e District, then analyze problems that occur among MSMEs and determining programs to overcome existing problems. From the analysis that has been determined, the solution that can be implemented is to provide socialization and assistance in creating NIBs through OSS for Micro, Small and Medium Enterprises. The assistance activity in creating Business Identification Numbers (NIB) for MSMEs in the Salama area, Na'e sub-district, Bima city, succeeded in increasing business actors' understanding of the importance of business legality. Of the MSMEs in Nae Village, especially the Salama Ward, it was recorded that 20 had succeeded in having NIBs where making NIBs through the OSS system can be done easily and quickly. This mentoring activity provides wider access to government assistance and capital.